THE RELATIONSHIP BETWEEN NUTRITION CONSCIOUS FAMILY BEHAVIOR AND STUNTING INCIDENTS IN TODDLERS IN THE JELBUK HEALTH CENTER WORKING AREA, JEMBER REGENCY - Kustin; Oktavia, Evi Tri Wahyuni; Hidayati, Ainul (Journal of Nursing Periodic, 2025)
Background: Stunting is one of the nutritional problems affecting Indonesian toddlers. Inadequate nutritional intake and nutritionally conscious family behavior are one of the trigger factors. The prevalence of stunting in Jember Regency according to SSGI in 2022 is still at 34.9%, which is the highest figure in East Java. From the results of a preliminary study conducted by researchers, it was found that 356 children (17.8%) were stunted in the weighing month of February 2023 and 381 children (18.46%) were stunting in the weighing month of August 2023. KADARZI behavior plays an important role in the growth process in toddler. Method: The method in this research is quantitative correlational with an observational approach and a cross-sectional research design. The total sample was 95 respondents using cluster sampling techniques with the Slovin formula. The measurement instrument for this research uses a questionnaire, then assesses stunting in toddlers using microtoise measurements and converts it into a standardized value (Zscore) using the WHO- 2005 anthropometric standards for toddlers. Statistical analysis uses Chi Square with significance <0.05. Results: The results of this study show that the majority of respondents do not behave as stunted, 67 (70.5%) respondents, and the majority of respondents experience stunting, 65 (68.4%) respondents. The results of the Contingency Coofficient statistical test show that the Approximate Significance value= 0.000 so there is a significant relationship between KADARZI behavior and the incidence of stunting in toddlers aged 6-59 months. Discussion: It is hoped that mothers who have toddlers can apply the 5 indicators of KADARZI Keywords: KADARZI behavior, Stunting, Toddlers